A Panic-Prone Pack? : The Behavior of Emerging Market Mutual Funds - Gelos, R. (IMF Working Papers; Working Paper ;, 2000)
This paper explores the behavior of emerging market mutual funds using a novel database covering the holdings of individual funds over the period January 1996 to March 1999. An examination of individual crises shows that, on average, funds withdrew money one month prior to the events. The degree of herding among funds is statistically significant, but moderate. Herding is more widespread among open-ended funds than among closed-end funds, but not more prevalent during crises than during tranquil times. Funds tend to follow momentum strategies, selling past losers and buying past winners, but their overall behavior is more complex than often suggested.